2013
DOI: 10.1097/yct.0b013e31827e568c
|View full text |Cite
|
Sign up to set email alerts
|

Transient Hemiparesis (Todd’s Paralysis) After Electroconvulsive Therapy (ECT) in a Patient With Major Depressive Disorder

Abstract: We report the case of a 50-year-old man who exhibited transient left hemiparesis (Todd's paralysis) after electroconvulsive therapy, which completely resolved within 10 minutes. Subsequent neurological evaluation was unremarkable for discrete etiologies for this event, other than Todd's paralysis. We review the literature of this phenomenon in association with electroconvulsive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Previous reports mostly document a unilateral stimulus associated with post ECT Todd's paralysis [2][3][4][5][6][7][8], whereas this patient had bilateral stimulation. We speculate that the addition of a second stimulus at maximum current resulting in a second prolonged seizure was the likely culprit of Todd's paralysis in our patient.…”
Section: Financial Disclosuresmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous reports mostly document a unilateral stimulus associated with post ECT Todd's paralysis [2][3][4][5][6][7][8], whereas this patient had bilateral stimulation. We speculate that the addition of a second stimulus at maximum current resulting in a second prolonged seizure was the likely culprit of Todd's paralysis in our patient.…”
Section: Financial Disclosuresmentioning
confidence: 98%
“…
Todd's paralysis), can only occur as a diagnosis of exclusion. The development of hemiplegia following ECT necessitates a timely and extensive evaluation with significant healthcare resource consumption.Upon searching PubMed for transient paralysis and electroconvulsive therapy, there appears to be very little report of this phenomenon in the literature [2][3][4][5][6][7][8]. Most reports of transient hemiplegia are in the context of unilateral electrical brain stimulation with resulting contralateral transient hemiplegia.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its pathogenesis may be similar to TP demonstrated following a spontaneous seizure. Compared with TP associated with epilepsy, the duration of TP that occurs in the context of ECT is shorter [31]. In particular, previous studies have shown that transient paralysis of the left face lasting 20 minutes has occurred in the content of electrical stimulation to the contralateral side of the brain [32].…”
Section: Etiologymentioning
confidence: 99%
“…These cases involved symptoms of facial paralysis, hemiparesis, and dysarthria, with symptom resolution occurring between 10 minutes and 10 days after onset. In 3 of 4 cases, neurology was consulted 2–4 . In 2 of the 4 cases, ECT treatment was continued after Todd paralysis, 2,5 and 1 case described switching the patient from unilateral to bilateral ECT, with no further complications 2 .…”
mentioning
confidence: 99%